2015
DOI: 10.1126/sciadv.1400173
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of metastability and hidden phases in correlated electron crystals visualized by femtosecond optical doping and electron crystallography

Abstract: Using femtosecond photodoping and crystallography to explore metastable and hidden quantum phases in tantalum disulfide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 55 publications
12
111
0
Order By: Relevance
“…The most significant difference between the two experiments is the photon energy of the pump, which is two times larger for the present experiment. The time-resolved electron diffraction work of Han et al [8] showed very different threshold behavior for photoinduced phase transitions starting from the C-CDW phase for 800 nm versus 2500 nm pumping wavelengths, even after correcting for differences in absorption. This suggests that the occurrence of the photoinduced phase transitions does not depend on the overall absorbed energy density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant difference between the two experiments is the photon energy of the pump, which is two times larger for the present experiment. The time-resolved electron diffraction work of Han et al [8] showed very different threshold behavior for photoinduced phase transitions starting from the C-CDW phase for 800 nm versus 2500 nm pumping wavelengths, even after correcting for differences in absorption. This suggests that the occurrence of the photoinduced phase transitions does not depend on the overall absorbed energy density.…”
Section: Discussionmentioning
confidence: 99%
“…Below 180 K, these discommensuration regions disappear and the material becomes insulating, forming the commensurate (C) phase. Femtosecond laser excitation has been shown to trigger transitions from the C and NC phases to the NC and I phases, respectively [8,9]. The photoinduced NC to I transition is the focus of the present work.…”
Section: Introductionmentioning
confidence: 96%
“…In this strongly nonequilibrium condition, the thermodynamic ground state may become less stable than its counterparts and metastable new phases may emerge34. Characterizing the nonequilibrium transformations between two thermodynamic phases directly or through a metastable phase indirectly may provide valuable insights regarding the nature of these states, the interactions, and the active coordinates involved in these phase transitions5.…”
mentioning
confidence: 99%
“…The electron pumping mechanism across a structural phase transition that we observe for Cu 2 S nanoplates will no doubt also be operating in other metastable and nonequilibrium phases as well, and for metal-insulator phase transitions in general in nanoparticles of complex materials (26)(27)(28).…”
Section: Significancementioning
confidence: 99%